منهج النبي صل االله عليه وسلم في التعليم: دراسة تحليلية في الصحيحين - مسكري ، إبراهيم محمد علي سالم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study deals with exploring and analyzing of the prophetic approach to education at a large scale and it is summed up in illustrating its main dimensions, intentions of prophetic teaching, its characteristics and aspects. It also aims to prove that the versatilities of prophetic approach to education with respect to the depth of its intentions and the abundance of its methods and means; thus, enhancing adherence to it to attain the best means to benefit from it while many Muslims are preoccupied with western theories of education. The importance of such studies lies in the reflection and reasoning in Al Sunna Al Sahiha in a scientific way in order to extract new approaches and educational methodologies. The method employed in research is the inductive one of extrapolating and tracking the hadiths of Saheeh al-Bukhari and Sahih Muslim to extract the hadiths that are related to the subject. While the analytical method is used to devise means and approaches, analyze the texts, explain them, mention their benefits, and relate them to reality in order to employ them in modern curricula. The study concluded with several results; the most important of which is that the Prophet was keen to educate his companions to instill great principles to build Islamic civilization. Therefore, his teaching was not limited to religious purpose only, but it also included financial and social aspects in order to insure prosperity of Muslims in all aspects. The study has also substantiated the inclusiveness of the approaches of prophet's methods to the mental, linguistic, emotional and practical skills. Hence, he was really considerate of the different social classes the learners came from, and showed the Prophet's care in the use of visual means to clarify the meanings and ideas to the learners' mind.